The Role of Metaphor in Idiom Interpretation: Further Ruminations - Kovalyuk, Yu. (Science and Education: A New Dimension. Philology, 2020)
One of the primary concerns of English linguistics regarding idioms and idiomaticity consists in finding grounds for divorcing idioms from the generative grammar theory (Fraser, 1970; Katz, 1973; Swinney and Cutler, 1979; Wood, 1986). According to this strand of thought, idiomatic expressions are semantically non-compositional and fully fixed in their lexico-grammar representations. Quite possibly, credit is due to cognitive grammar (Langacker, 1987; 2008) and construction grammar (Fillmore, 1988; Goldberg, 1995; 2006; Hilpert, 2014; Herbst, 2015) for providing the backdrop against which the compositional model of idiomaticity (Gibbs, 1990; 1995; 2007; Cacciari and Glucksberg, 1991; Glucksberg, 1993; Cacciari, 2014) has emerged. It argues that many idioms, contrary to generative linguistics vantage point, are flexible and amenable to lexical and syntactic transformations. This paper explains theoretical concepts along with practical examples, which may shed light on the role of metaphor in the analyzability and decomposability of idiomatic expressions. Firstly, we explain how the concept of metaphorical regularity vs. metaphorical irregularity, applied to the study of idioms, allows distinguishing between regular and irregular metaphors incorporated by idiomatic expressions. Secondly, we analyze the notion of metaphorical asymmetry, which, as regards idioms and idiomaticity, refers to uneven distribution of figurative meanings among idiom parts. Thirdly, we focus on some particular facets of conceptual metaphor, such as cross-domain mappings, metaphorical concepts, and metaphorical entailments. We conclude the discussion with extended idiomatic metaphor, which is an amalgam of micro-metaphors bundled around the base metaphor of an idiom in a literary text. Hence, our principal argument is that the aforementioned metaphorbased linguistic concepts are important idiom processing tools in psycholinguistics. Language users may find them advantageous when trying to work out the meaning of unfamiliar metaphor-derived idiomatic expressions in discourse.
Keywords: idiom, interpretation, compositionality, metaphorical regularity, metaphorical asymmetry, conceptual metaphor, extended idiomatic metaphor